2013
DOI: 10.1016/j.canep.2013.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the proportion of esophageal squamous cell carcinoma cases attributable to tobacco smoking and alcohol consumption

Abstract: Objective: Alcohol and tobacco are the two major established environmental factors associated with squamous cell carcinoma of the esophagus (ESCC). However, the prevalence of these exposures differs substantially between men and women. Moreover, the prevalence of smoking has declined in recent years, whereas per capita consumption of alcohol has remained steady in both sexes. Quantifying the burden of ESCC attributable to these causal factors is necessary to inform potential preventive strategies. Methods: We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(52 citation statements)
references
References 17 publications
(25 reference statements)
2
47
1
Order By: Relevance
“…The WHI subjects were recruited for three clinical trials and one observational study. There are well-known sex differences in smoking and drinking behaviors and their consequences (Pandeya et al, 2013;Cosgrove et al, 2014;White et al, 2015), and the current study provided novel important data regarding the role of alcohol and tobacco use and their genetics in women's health.…”
Section: Introductionmentioning
confidence: 76%
“…The WHI subjects were recruited for three clinical trials and one observational study. There are well-known sex differences in smoking and drinking behaviors and their consequences (Pandeya et al, 2013;Cosgrove et al, 2014;White et al, 2015), and the current study provided novel important data regarding the role of alcohol and tobacco use and their genetics in women's health.…”
Section: Introductionmentioning
confidence: 76%
“…Risk factors for adenocarcinoma include male sex, advancing age, white race, gastroesophageal reflux disease, Barrett's esophagus, obesity, and smoking [4]. Alcohol and smoking are the main risk factors for squamous cell carcinoma [5].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Zhu et al (2012) observed that incidence of SPC in the EC patients was disproportionally higher in male than in female. The reason why SPC occurred in EC patients with male preponderance was not totally clarified yet, but it was generally deemed that tobacco and alcohol consumption played a crucial role in the prevalence of EC with the gender differences (Pandeya et al, 2013;Prabhu et al, 2014). Therefore, lifestyle changes such as restriction of cigarette smoking and alcohol consumption were suggested as one of the preventive strategies of developing SPC in EC patients (Jemal et al, 2011;Tang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%